Clinical Management and Therapeutic Strategies for the Thyroid-Associated Ophthalmopathy: Current and Future Perspectives - Mishra, Shailja; Maurya, Vimal K; Kumar, Swatantra; Kaur, Apjit; Saxena, Shailendra K (Current eye research, 2020)
TAO is an organ specific autoimmune disease associated with thyroid, and inflammation of the orbit and periorbital tissues, which is different from systemic autoimmune diseases such as SLE. However, Grave's disease is a kind of systemic autoimmune syndrome which might involve the thyroid, the eye ball and the anterior tibial tissue. Considering the inexplicable understanding of TAO pathogenesis, the disease worsens for the patients. Therefore, this manuscript provides insights into the recent advancements of clinical features, epidemiology, pathogenesis with gene-interactions, diagnosis, including available and novel treatment options for TAO, based on available data including RCTs, meta-analyses, and systematic reviews. Articles with clinical features, epidemiology, pathogenesis, diagnosis, and treatment of the disease were thoroughly studied. To perform the gene expression and pathway analysis, articles were searched on PubMed, MEDLINE Cochrane Library and ClinicalTrial.gov from 1982 to 2020. To predict novel TAO-specific therapeutic molecule, structure-based drug design (SBDD) was performed. We observed gene expression and pathway analysis and SBDD approaches might bring new insights in the field of TAO pathogenesis, diagnosis, and treatment. A genome-wide map of human genetic interactions revealed involvement of crucial cell-signalling pathways, such as TNF-mediated signalling pathway, type-I interferon signalling pathway, toll-like receptor signalling pathway, transforming growth factor-beta receptor signalling pathway etc. Recently, FDA-approved teprotumumab a breakthrough, first drug for the treatment of active thyroid eye disease, which reduces proptosis and the need for orbital decompression surgery. Furthermore, our SBDD results revealed that cost-effective Curcumin, Withaferin A, Resveratrol, Scopolamine, Quercetin, and Berberine may have significant binding affinity for hyaluronan protein and may be exploited for therapeutic purposes in TAO. Considering the increasing risk and nature of disease, novel drug therapies and markers for prognosis need to be investigated. Moreover, evidence-based non-invasive/minimal surgical therapies should be developed for the better management of the disease. ADIPOQ: Adiponectin; CAS: Clinical Activity Score; CCL5: C-C Motif Chemokine Ligand 5; CT: Computed Tomography; DON: Dysthyroid Optic Neuropathy; EUGOGO: European Group of Graves' Orbitopathy; FDA: U.S. Food and Drug Administration; FOS: Fos Proto-Oncogene, AP-1 Transcription Factor Subunit; HLA: Human Leukocyte Antigen; HLA-DRA: Major Histocompatibility Complex, Class II, DR Alpha; ICAM1: Intercellular Adhesion Molecule 1; IFNG: Interferon Gamma; IGF-1: Insulin-like Growth Factor 1; IGF-1R: Insulin-like Growth Factor-1 Receptor; IL12B: Interleukin 12B; IL23R: Interleukin 23 Receptor; IL6: Interleukin 6; IOP: Intraocular Pressure; IRF1: Interferon Regulatory Factor 1; IRF5: Interferon Regulatory Factor 5; IRF7: Interferon Regulatory Factor 7; IRF9: Interferon Regulatory Factor 9; JUN: Jun Proto-Oncogene, AP-1 Transcription Factor Subunit; JUNB: JunB Proto-Oncogene, AP-1 Transcription Factor Subunit; MHC: Major Histocompatibility Complex; MRI: Magnetic Resonance Imaging; NFKB1: Nuclear Factor Kappa B Subunit 1; NFKBIA: Nuclear Factor Kappa B Inhibitor Alpha; OADSCs: Orbital Adipose Derived Stromal Cells; PDGFB: Platelet Derived Growth Factor Subunit B; PPARG: Peroxisome Proliferator Activated Receptor Gamma; RANTES: Regulated on Activation Normal T cell Expressed and Secreted; RARA: Retinoic Acid Receptor Alpha; RCTs (Randomized Controlled Trials; SLE: Systemic lupus erythematosus; SOCS3: Suppressor of Cytokine Signaling 3; STAT1: Signal Transducer and Activator of Transcription 1; TAO: Thyroid-Associated Ophthalmopathy; TED: Thyroid eye disease; TGFB1: Transforming Growth Factor Beta 1; TGFB2: Transforming Growth Factor Beta 2; TGF-β: Transforming Growth Factor-beta; TLR7: Toll like Receptor 7; TLR9: Toll like Receptor 9; TNFRSF18: Tumor Necrosis Factor Receptor Superfamily Member 18; TNFSF11: Tumor Necrosis Factor Receptor Superfamily Member 11; TNF-α: Tumor Necrosis Factor-alpha; TSHR: Thyroid Stimulating Hormone Receptor; TSIs: Thyroid Stimulating Immunoglobulin; WNT5A: Wingless-Type MMTV Integration Site Family, Member 5A.